Third-Country Equivalence and Access to the EU Financial Markets Including in Case of Brexit. Issue 2 (10th October 2018) - Wymeersch, Eddy
Abstract: After Brexit, the UK will become a third country. In the absence of a transitional agreement, its access to the European Union (EU) markets will be conditioned on meeting the condition of 'equivalence of regulation and supervision' as laid down in many EU regulations. The regime applicable will be the same as that of all third countries, as has been applied in many fields. Several other approaches may apply, but equivalence is one of the more efficient and less costly ones. In many cases, the key to equivalence lies formally in the hands of the Commission: the absence of a formal equivalence Commission decision may constitute a serious obstacle, in this case, to the UK continuing to offer financial services on the EU markets. If transition agreements are insufficient, a last minute opening of the markets on the basis of the equivalence regime may offer a provisional solution.